Instantiation. (8th December 2021) - Marmodoro, Anna
What is it, metaphysically, for a universal to be instantiated in a concrete particular? Philosophical controversy has been ongoing since the beginning of philosophy itself. I here contribute a novel account of instantiation developed on the basis of Aristotelian premises (but departing from the mainstream interpretation according to which Aristotelian universals are instantiated by 'combining' hylomorphically with matter). The key stance is that for Aristotle each substance is one, i.e. single (in addition to also being a non-recurrent particular). I show that for Aristotle, the oneness of substances is primitively assumed, and, importantly, cannot be derived from composition of parts, not even holistic composition. Parts undermine oneness. It follows that instantiated properties are not parts of substances. However, if not parts of the substances they are in, what are they? Aristotle shows they are qualifications of the substances they are in. Don't qualifications undermine the singleness of a substance? I show that Aristotle makes sure they do not. The way he does it is new, then and now. Instantiated properties are 'hybrid' entities: they sacrifice their own discreteness qua properties, while adopting the discreteness of the metaphysical subject they qualify, i.e. the substance. But then, how can a universal quality recur in many substances, if, when instantiated, it assimilates the discreteness of each of these substances? This is a key Aristotelian stance: the quality recurs, not its qualifications . Qualities are abstracted from their instances in similar objects, e.g. 'wisdom' is abstracted from many 'wise' people; 'wisdom' is individuated bottom-up from its instances, by abstraction.